The Role of Cash Holding, Good Corporate Governance, Sales Growth, and Working Capital Turnover on Company Value: Empirical Evidence from the Basic Materials Sector on the Indonesia Stock Exchange - Sisca Contesa; Theresia Contesa (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the determinants of firm value, proxied by Price to Book Value (PBV), by examining the effects of cash holding, good corporate governance, sales growth, and working capital turnover on companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX). The sample was selected using a purposive sampling method, resulting in 26 observed firms. The study employs secondary data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). Data analysis was conducted using multiple linear regression with IBM SPSS version 26. The findings reveal that cash holding and working capital turnover have a positive but insignificant effect on Price to Book Value, while good corporate governance and sales growth show no significant influence on firm value. These results indicate that internal corporate factors have not yet fully explained variations in market valuation among basic materials companies in Indonesia, suggesting the need for further research to explore additional variables that may affect firm performance in the capital market context.